“Relationships of Care”: Care and Meaning in Canadian Academic Librarian Work during COVID-19 - McLay Paterson, Amy; Eva, Nicole (Partnership, 2022)
In March and April 2021, we conducted semi-structured interviews with academic librarians from across Canada about their experiences working through COVID-19 thus far. Topics included workload, collegiality, and overall satisfaction with their working conditions during a pandemic. Themes emerged around job scurity, meaningful work, workload shifts, working from home, relationships with colleagues and administrators, and hopes for the future. While individual experiences varied greatly, the biggest uniting factor was the care and deliberation that characterized both our participants’ framing of work that was meaningful to them as well as their ideal relationships with colleagues and administrators. This research connects to previous literature on vocational awe and emotional labour in libraries. For librarians, this study connects isolated individual situations with the overall picture of what our work looked and felt like during the COVID-19 pandemic. For library administrators, we have identified some general trends, which can provide insight in the areas of communication, flexibility, and institutional support as we work toward a post-pandemic new normal.